Exploring Dimensions of Trauma-Linked Somatic Complaints in Refugees: A Qualitative Study in Canada - Wandzilak , Przemyslaw; Isci , Onur; Castro-Medina, Paulo (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study aimed to explore the dimensions of trauma-linked somatic complaints among refugees, focusing on how trauma is embodied, expressed, and managed in the context of displacement.Methods and Materials: A qualitative research design was employed, using semi-structured in-depth interviews with 17 refugees residing in Canada. Participants were recruited through community networks and refugee support organizations. Interviews, lasting 60–90 minutes, were conducted with the aid of professional interpreters where necessary and continued until theoretical saturation was reached. All interviews were audio-recorded, transcribed verbatim, and analyzed using NVivo 14 software. A thematic analysis approach was applied, involving iterative coding, categorization, and theme development to capture the range of trauma-linked somatic experiences.Findings: Four overarching themes emerged from the analysis: (1) Bodily manifestations of trauma, including chronic pain, gastrointestinal distress, sleep disturbances, neurological symptoms, cardiovascular complaints, and persistent fatigue; (2) Psychological-somatic linkages, where anxiety, depression, flashbacks, and emotional suppression were embodied through physical discomforts; (3) Sociocultural and contextual influences, including cultural idioms of distress, stigma, access barriers to healthcare, post-migration stressors, and the role of community and faith; and (4) Coping and healing strategies, ranging from medical help-seeking and alternative remedies to mindfulness, community-based support, resilience-building, and avoidance. Participants’ narratives highlighted the embodied nature of trauma and the interplay between pre-migration trauma and post-migration challenges in shaping somatic complaints.Conclusion: The study underscores that trauma-linked somatic complaints among refugees are complex, multifaceted, and shaped by cultural and contextual factors. Recognizing these complaints as legitimate trauma expressions is crucial for trauma-informed healthcare and fair asylum adjudication. Integrating medical, psychological, and social approaches, alongside culturally sensitive and community-based interventions, is essential to address the embodied dimensions of refugee trauma.